Substautiation of kineziological methods of rehabilitation of children suffering from scoliotic disease - Tamozhanskaya G.V (Kharkov National Pedagogical University, 2013)
Shows the results of screening studies of the frequency and severity of violations of scoliotic spine. It is noted that this pathology occurs in any population, regardless of the race, and geographic location of its location. Installations constant manifestation of this disease in the range of 0.5% -3% by weight of observations. This indicates that these morphologic variations in the total population of three sigmoid zone are deviations from the average functional characteristics oscillation growth period. In order to ensure early diagnosis and prevention organization corrective measures necessary to systematically monitor physical development, physical fitness and physical condition of the controlled population. Diagnosing the predisposition of children makes it possible means of prevention kinesiology scoliotic prevent violations of I - II degree.